Beating the odds (1): intergenerational social mobility from a human capital perspective - Jonathan Gershuny (University of Essex, Institute for Social and Economic Research (ISER), 2002)
The objective of this paper is to use a human capital measure as the positional indicator in an investigation of trends in equality of intergenerational life chances. The BHPS retrospective work and employment history files provide a continuous account of respondents occupational positions throughout their adult lives, and also records of their parents employment circumstances (if any) when the respondents were aged 14. In a first series of analyses, a conventional Goldthorpe 3*3 mobility model is compared to a categorical model grouping fathers and children into human capital quintiles. The Goldthorpe analysis shows some increase in equality, over mid 20th century birth cohorts, whereas the human capital model shows no clear trend. The difference is explained by: (1) the exclusion of non-employed women from the Goldthorpe model, where the human capital estimation covers all the BHPS respondents irrespective of employment status; and (2) the use of constant-sized quintile groups in the human capital model where the sizes of the Goldthorpe classes change over time. A second series of analyses relies on regression models, explaining childrens human capital scores at various ages in terms of their sex, birth cohort, fathers human capital and various transformations of, and interactions among, these variables. Instantiations of these models show diverging trends of growth in the predicted mean human capital of children of low- and of high-human capital fathers over successive birth cohorts from the 1930s to the 1960s-implying a regular increase in the inequality of intergenerational life chances in Britain over this period.
Keywords: 330